Drug delivery systems for osteomyelitis - Bastari, Kelsen (2013)
Osteomyelitis or bone infection is one of the most serious complications in orthopedics due to its difficulty to treat, associated with poor blood circulation of the infected bone. The objective of this study is to develop a particulate system that not only sustains the drug release up to 4-6 weeks to eradicate completely the infection, but also possesses properties close to bone tissues to aid bone regeneration. This was realized by fabricating carrier system which consists of a polymeric core and calcium phosphate (CaP) ceramic coating through a surface adsorption-nucleation technique. The results obtained showed that some parameters such as type of surfactants, calcium and phosphate solution concentrations, and also stirring time affect the coating process to obtain a homogeneous and uniform coating. Drug loading and release study of antibiotics from these hybrid particles were investigated, and the results showed that the presence of CaP coating could reduce the burst release and slow down the first phase of the release which was governed by diffusion. It was also observed that this effect was more pronounced on hydrophilic drug as compared to amphiphilic drug. In vitro bacterial study demonstrated the capability of these antibiotic-loaded hybrid particles to inhibit the growth of bacteria as well as inhibit and deteriorate biofilm up to 4 weeks. In addition, surface modification of the particles by bone-targeting ligand, bisphosphonate (BP), was conducted to facilitate delivery of the drug to the site of bone infection. The results achieved showed promising results as the BP-modified particles increased the affinity towards bone surface, indicating the potential to help localize the particles to bone infection site.